68Ga-DOTATOC PET in Extracranial Hepatic and Bone Metastasis of Atypical Refractory Meningioma: A Case Report. (February 2023) - Ghomari, Cherifa Fazila; Bender, Laura; Lhermitte, Benoît; Noël, Georges; Namer, Izzie Jacques; Bund, Caroline
Abstract: A falcine meningioma was diagnosed in a 66-year-old woman and was treated by surgery and 2 times by radiotherapy during 9 years of follow-up with the diagnosis of atypical meningioma. Three months after the last radiotherapy, incidental liver lesions were detected on chest CT realized for suspected pneumonia. In view of the predisposing factors for meningioma metastases, 68 Ga-DOTATOC hepatic and cerebral PET/MRI was performed and completed by total body PET/CT demonstrating a somatostatin receptor 2 overexpression of the multiple liver lesions and several bone lesions. Biopsies from the liver and iliac bone confirmed the metastatic origin of meningioma.